Subseasonal Vacillations in the Winter Stratosphere. Issue 9 (5th May 2020) - Hardiman, S. C.; Scaife, A. A.; Dunstone, N. J.; Wang, L.
Abstract: Simple models of wave‐mean flow interaction in the Northern Hemisphere winter stratosphere suggest the existence of subseasonal vacillations in the strength of the polar vortex. Here, we define a sinusoidal fit to the daily deseasonalized stratospheric wind. A suitable fixed period and amplitude for the sine waves is identified. Their mean value, equivalent to polar vortex strength, and phase, equivalent to the timing of sudden stratospheric warmings during winter, varies from year to year. These vacillations explain much of the subseasonal and interannual variability in the monthly mean vortex strength and, consistent with wave‐mean flow interaction theory, their amplitude correlates positively with the magnitude of winter mean planetary wave driving. Furthermore, they allow skillful prediction of the vortex strength one month ahead. Identifying and understanding this subseasonal variability has potential implications for winter seasonal forecasts, as the December–February mean behavior may miss important subseasonal events. Key Points: Simple sine wave fits capture two thirds of interannual variance in monthly Northern Hemisphere winter stratospheric polar vortex strength Amplitude of these vacillations increases with planetary wave driving, consistent with wave‐mean flow interaction theory Simple model skillfully predicts the stratospheric polar vortex strength at one month lead time